The Effect of Character, Capacity, and Collateral on Causing Non-Perfoming Loans in Banking in Indonesia - Raynaldi, Raynaldi; Irwan Sutirman Wahdiat (Dinasti Publisher, 2025)
This research seeks to analyze, identify, and assess the impact of character, capacity, and collateral on the factors leading to non-performing loans in the city of Cirebon, using banks as the analytical unit. A non-performing loan refers to credit that is overdue for a specific duration, typically exceeding 90 or 180 days. Such loans arise when the borrower fails to meet their repayment obligations as per the terms agreed upon by both parties. Non-performing loan denotes a situation where a client is unable to settle their debts with the bank punctually. This study employs a quantitative approach to select the sample, which consists of 48 bank employees in Cirebon, analyzed through classical assumption methods to test the research hypothesis. The statistical analysis indicates that the character variable significantly influences the incidence of non-performing loans, the capacity variable has a notable influence on the occurrence of non-performing loans, and the collateral variable also significantly impacts the occurrence of non-performing loans.